Ensino de frações e da função quadrática: uma abordagem alternativa ao modelo tradicional - Barboza, Wanderlânyo de Lira (2013)
This research aims to provide a discussion after the presentation of two experiments that were conducted intervention trying to give a grant to a pedagogical alternative to the traditional model. As this is a descriptive research, we aim not indicate paths or presenting solutions to problems, and for having in his rise characteristics of a case study, we examine in making only the reports of our experience and base our actions without major theoretical debates. For this, we present the memorial to draw in the reader a profile of the author of the study and describe our experience in the discipline of mandatory intervention Supervised III, offered by the Federal University of Paraíba. After that, we brief quotations and theoretical debates, where we highlight Japiassu (2006), Pavanello (2004), Kleiman and Morais (1999), among others, to write on Contextualization, Interdisciplinary, Reading and Troubleshooting. We also present our experience of intervention about content Quadratic Function in a class of high school and eventually we have our final considerations.